2016
DOI: 10.1002/qua.25083
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the interaction of fluorinated dimethyl ethers and the ClF and HF molecules. Comparison between halogen and hydrogen bonds

Abstract: A theoretical study of the halogen-bonded complexes formed between fluorinated dimethyl ethers (n F 5 0-4) and ClF is carried out using the wB97XD method combined with the 6-31111G(d,p) basis set. The properties of the complexes are compared with the corresponding properties of the hydrogenbonded complexes formed between the same electron donors and HF. The optimized geometries, the interaction energies, relevant natural bonding orbital characteristics along with some vibrational data are calculated. The analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 80 publications
(104 reference statements)
6
17
0
Order By: Relevance
“…The charge on the N atom also decreases when the H atoms of NH 3 are substituted by CH 3 groups, being equal to −0.807 e in NH 2 CH 3 and −0.391 e in N(CH 3 ) 3 . Our calculations are in quantitative agreement with previous calculations carried out at the HF level with a 3‐21G basis set . These calculations have shown that the Mulliken charges and the V s,min values decrease with increasing methyl substitution on NH 3 .…”
Section: Resultssupporting
confidence: 91%
“…The charge on the N atom also decreases when the H atoms of NH 3 are substituted by CH 3 groups, being equal to −0.807 e in NH 2 CH 3 and −0.391 e in N(CH 3 ) 3 . Our calculations are in quantitative agreement with previous calculations carried out at the HF level with a 3‐21G basis set . These calculations have shown that the Mulliken charges and the V s,min values decrease with increasing methyl substitution on NH 3 .…”
Section: Resultssupporting
confidence: 91%
“…In an effort to comprehend this behavior, the redshift in the acetylenic C−H stretching frequencies were plotted against other components of the SAPT2 interaction energy, such as induction, dispersion, and exchange repulsion, and the results are presented in Figure A–C. Similar correlations between various energy components for a variety of hydrogen‐bonded systems have been reported in the literature . It can be seen from Figure that the frequency shifts are linearly correlated with induction energy, which is a second‐order electrostatic effect.…”
Section: Resultssupporting
confidence: 65%
“…Similar correlations between various energy componentsfor avariety of hydrogen-bondeds ystems have been reported in the literature. [45][46][47][48][49][50] It can be seen from Figure 7t hat the frequency shifts are linearly correlated with induction energy,w hich is as econd-order electrostatic effect. The linear correlation suggestst hat even second-order electrostatic effects can influence the vibrational frequency shift.…”
Section: Resultsmentioning
confidence: 99%
“…SAPT method slightly overestimated the interaction energy compared with MP2 method while the change trend is the same. The interaction energies E int of the complexes are decomposed into four aspects: electrostatic interaction E elst , exchangeenergies E exch , induction energies E ind , and dispersion energies E disp . As shown in Table , all the E elst , E ind , and E disp are attractive while the E exch is repulsive as expected.…”
Section: Resultsmentioning
confidence: 99%